The pattern of vancomycin, gentamycin, and meropenem prescriptions for the inpatients of a regional public hospital in Yogyakarta, Indonesia - Mutiara Herawati; Mir-a Kemila; Putri Anggriani; Nur Mardhiyah; Siti Maulida (Jurnal Ilmiah Farmasi, 2022)
Background: The mechanism of action of gentamycin is inhibiting protein synthesis inside bacteria. Meropenem and vancomycin have the same mode of action that inhibit bacterial cell wall activity. Antibiotic resistance occurs when antibiotic use does not follow the guidelines. Therefore, this study aims to determine how vancomycin, gentamycin, and meropenem are prescribed in a regional public hospital. Objective: This study aimed to evaluate the prescription of vancomycin, gentamycin, and meropenem in Yogyakarta Regional Public Hospital in 2017. Methods: This research employed a descriptive analysis with a cross-sectional design. The study was conducted to describe the profiles of vancomycin, gentamycin, and meropenem utilization. Data collection was performed retrospectively using patients’ medical record data including the diagnosis, dosage, and duration of administration.Results: The study showed that the total number of patients who received aminoglycoside: meropenem: vancomycin antibiotics in 2017 and met the research criteria was 6:8:24. According to the diagnosis, gentamycin was used for post-operation (75%), then sepsis and encephalitis. Meropenem was used for sepsis with a percentage of 67% while vancomycin was for endocarditis, intraabdominal, MRSA, cellulitis, pneumonia, and sepsis. Based on the appropriate dosage in the guidelines, the prescribing of gentamycin and meropenem resulted in 100% properness and 69.23% for vancomycin. For the duration of appropriate utilization, it was found that the most prolonged use was in patients given meropenem for 29 days, and the fastest use was a day for patients using vancomycin. Conclusion:Vancomycin, gentamycin, and meropenem had the appropriate dosage. However, discrepancies were still found in the indication and duration of the treatment using these antibiotics.Keywords: Vancomycin, gentamycin, meropenem, antibiotics